2013
DOI: 10.1038/bjc.2013.637
|View full text |Cite|
|
Sign up to set email alerts
|

DICER1 hotspot mutations in non-epithelial gonadal tumours

Abstract: Background: Non-epithelial gonadal tumours largely comprise sex cord-stromal tumours (SCSTs) and germ cell tumours (GCTs). Specific somatic mutations in DICER1, a microRNA maturation pathway gene, have been identified in these tumours. We conducted a study that aimed to confirm, refine and extend the previous observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 32 publications
(56 reference statements)
5
102
0
1
Order By: Relevance
“…1). Previous studies have found frequent DICER1 p.E1705-D1709 and p.D1810-E1813 mutations in Sertoli-Leydig cell tumors (3,28). However, no DICER1 mutations were detected in the two patients with Sertoli-Leydig cell tumors.…”
Section: Resultsmentioning
confidence: 67%
“…1). Previous studies have found frequent DICER1 p.E1705-D1709 and p.D1810-E1813 mutations in Sertoli-Leydig cell tumors (3,28). However, no DICER1 mutations were detected in the two patients with Sertoli-Leydig cell tumors.…”
Section: Resultsmentioning
confidence: 67%
“…DICER1 mutations are associated with pleuropulmonary blastoma, which is the most common lung tumor of infancy and early childhood, as well as with embryonal rhabdomyosarcoma of the uterine cervix, renal tumors, thyroid nodules and carcinoma, nasal chondromesenchymal hamartoma, ciliary body medulloepithelioma, pineoblastoma, and pituitary blastoma. 7,[10][11][12][13][14][15][16][17][18] Typically, these tumors have biallelic DICER1 mutations that are composed of a loss of function in one allele and a missense mutation in the RNase IIIb domain. Biallelic loss of function and missense RNase IIIb DICER1 mutations result in systemic loss of 5p-microRNAs that precludes regulation of growthpromoting gene programs.…”
Section: Dicer1mentioning
confidence: 99%
“…Notably, although macrocephaly is common and severe in CS [11], it has recently been identified as a surprisingly common feature of the DICER1 syndrome as well (42% of mutation carriers are macrocephalic) [9]. The patient’s ovarian tumour was a malignant germ cell tumour, which would be highly unusual in the DICER1 syndrome [4]. To our knowledge, no cases of ovarian germ cell tumours have been reported in germ-line DICER1 mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no cases of ovarian germ cell tumours have been reported in germ-line DICER1 mutation carriers. However, there are reports of somatic DICER1 RNase IIIb mutations in these tumours [3, 4]. Given that the diagnosis of ovarian tumours is often challenging [18], it should be kept in mind that in certain instances, DICER1 mutation analysis may assist in distinguishing between the types of non-epithelial ovarian cancers [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation